All-in-one organic ligand for emitting perovskite nanocrystals: Efficient dispersion, photocurable and charge transporting capability - Cho, Na Young; Jang, Ji Won; Oh, Byeong M.; Seok, Gyeong Eun; Seo, Haewoon; Kim, Sang Wook; Kim, Jincheol; Kim, Eunsu; Kim, Eunha; Choi, Hyosung; Lee, Bo Ram; Choi, Jin Woo; et al. (Chemical Engineering Journal, 2024)
Perovskite nanocrystals (PNCs) have attracted considerable interest as next-generation display materials owing to their outstanding photoluminescence quantum yield (PLQY), wide color gamut, and narrow emission bandwidth. However, because of their weak stability against solvents, the patterning of PNCs remains a challenge. In this study, we developed functional organic ligands (AzL1-Th and AzL2-Th) for the fine pixelation of PNC displays. Functional ligands containing photocurable azide moieties exhibit good charge transport properties and fast and efficient photocrosslinking performance, while maintaining a high PLQY. Moreover, the crosslinked PNC light emitting diodes were successfully demonstrated using AzL1-Th. These results suggest the high potential of photocurable ligands for the micro-patterning of PNC films without film damages.
Keywords: Charge transporting; Narrow emission bandwidths; Organic ligands; Perovskite nanocrystal; Photo patterning; Photocurable; Photoluminescence quantum yields; Quantum dot ligand; Weak stability; Wide color gamut; Charge transport; Crosslinking; Perovskite nanocrystals; Photo-patterning; Quantum dot ligand